The helix-loop-helix protein Id1 controls stem cell proliferation during regenerative neurogenesis in the adult zebrafish telencephalon - Rodríguez Viales, Rebecca; Diotel, Nicolas; Ferg, Marco; Armant, Olivier; Eich, Julia; Alunni, Alessandro; März, Martin; Bally-Cuif, Laure; Rastegar, Sepand; Strähle, Uwe (Stem cells, 2015)
The teleost brain has the remarkable ability to generate new neurons and to repair injuries during adult life stages. Maintaining life-long neurogenesis requires careful management of neural stem cell pools. In a genome-wide expression screen for transcription regulators, the id1 gene, encoding a negative regulator of E-proteins, was found to be upregulated in response to injury. id1 expression was mapped to quiescent type I neural stem cells in the adult telencephalic stem cell niche. Gain and loss of id1 function in vivo demonstrated that Id1 promotes stem cell quiescence. The increased id1 expression observed in neural stem cells in response to injury appeared independent of inflammatory signals, suggesting multiple antagonistic pathways in the regulation of reactive neurogenesis. Together, we propose that Id1 acts to maintain the neural stem cell pool by counteracting neurogenesis-promoting signals. Stem Cells 2015;33:892-903